Is local air pollution concentration a moderator or mediator of the association between residential greenspace and pediatric asthma exacerbations? A longitudinal study of pediatric patients in Philadelphia, Pennsylvania - Yun-Ting Yen; Leah H. Schinasi; Brisa N. Sánchez; Steven Melly; Kari Moore; Christopher B. Forrest; Chén C. Kenyon; Michelle C. Kondo; Anneclaire J. De Roos (International Journal of Hygiene and Environmental Health, 2025)

Prediction of daily childhood asthma exacerbation from ambient meteorological, environmental risk factors and respiratory viruses, Philadelphia, PA, 2011 to 2016 - Wanyu Huang; Lucy F. Robinson; Amy H. Auchincloss; Leah H. Schinasi; Kari Moore; Steven Melly; Christopher B. Forrest; Chén C. Kenyon; Anneclaire J. De Roos (Environmental Science and Pollution Research, 2025)
Childhood asthma exacerbation has multiple risk factors that occur concurrently in the environment — including extreme meteorological conditions, air pollution, aeroallergens, and respiratory virus infections. Few studies have predicted asthma exacerbation based on multiple time-varying environmental risk factors, together. In this study, we constructed an autoregressive integrated moving average (ARIMA) model to predict “high-risk” days for childhood asthma exacerbation in Philadelphia, PA from 2011 to 2016, during the aeroallergen season of each year, using a total of 28,540 asthma exacerbation case events identified from electronic health record (EHR) data. We selected predictors from quantile weighted sum regression (gQWS), incorporating temporal lags and season-stratification (early- vs. late-season), which were entered subsequently into multivariable ARIMA models. We found that daily nitrogen dioxide (NO 2 ), as well as monthly rhinovirus and respiratory syncytial virus (RSV) infection levels, were higher on the predicted “high-risk” days, as compared to days with lower childhood asthma exacerbation risk. The model performed better for late-season asthma exacerbation (July to October) than for early season (March to June). Future work and continued research is needed to facilitate local health guidelines pertaining to childhood asthma exacerbation.

The Toxicology Investigators Consortium 2023 Annual Report - Adrienne Hughes; Alexandra Amaducci; Sharan L. Campleman; Shao Li; Mari Costantini; Meghan B. Spyres; Hannah Spungen; Jessica Kent; Alyssa Falise; Rachel Culbreth; Paul M. Wax; Jeffery Brent; et al. (Journal of Medical Toxicology, 2024)

Associations between neighborhood characteristics and child well-being before and during the COVID-19 pandemic: A repeated cross-sectional study in the Environmental influences on Child Health Outcomes (ECHO) program - Xueying Zhang; Courtney K. Blackwell; Janet Moore; Shelley H. Liu; Chang Liu; Christopher B. Forrest; Jody Ganiban; Annemarie Stroustrup; Judy L. Aschner; Leonardo Trasande; Sean C.L. Deoni; Amy J. Elliott; et al. (Environmental Research, 2024)

Evaluation of evidence for interaction between PM2.5 and aeroallergens on childhood asthma exacerbation in Philadelphia, PA, 2011 to 2016 - Wanyu Huang; Leah H. Schinasi; Chén C. Kenyon; Amy H. Auchincloss; Kari Moore; Steven Melly; Lucy F. Robinson; Christopher B. Forrest; Anneclaire J. De Roos (Environmental Research, 2023)

Development of a Benchmark Eddy Flux Evapotranspiration Dataset for Evaluation of Satellite-Driven Evapotranspiration Models Over the CONUS - John M. Volk; Justin Huntington; Forrest S. Melton; Richard Allen; Martha C. Anderson; Joshua B. Fisher; Ayse Kilic; Gabriel Senay; Gregory Halverson; Kyle Knipper; Blake Minor; Christopher Pearson; et al. (Agricultural and Forest Meteorology, 2023)